EFFICACY AND ECONOMICS OF PEST MANAGEMENT MODULES AGAINST BRINJAL SHOOT AND FRUIT BORER (LEUCINODES ORBONALIS) - S. BHUSHAN; H. K. CHAURASIA; RAVI SHANKER (The Bioscan, 2011)
Field experiments were carried out during Rabi season of 2009 - 10 and 2010 - 11 to evaluate the efficacy of pest management modules against brinjal shoot and fruit borer (Leucinodes orbonalis). The result on efficacy of modules revealed that minimum shoot and fruit damage (9.32 and 14.83 per cent, respectively) was observed in module having shoot clipping with alternate spraying of Multineem (1500 ppm) and Triazophos (35%) plus deltamethrin (1%). Maximum yield (210.5 q/ha) was also recorded in the same module. Minimum shoot and fruit damage was recorded in 3rd week of December.